Deterrence and delinquency: An analysis of individual data - Montmarquette, Claude (Journal of quantitative criminology, 1985)
Is commission of crime deterred by fear of arrest? Individual self-reported data on the commission of three crimes are analyzed in relation to perceived probabilities of arrest for more than 3000 French-speaking teenagers of the Montreal school population in 1974. The crimes are shoplifting, drug use, and stealing an item worth more than $50.00. In addition to the effect of the individuals' perceptions of the probability of arrest for the three crimes, age, sex, and previous arrest record are also taken into account. The data are all categorical. A multivariate log-linear probability model is estimated in order to test hypotheses concerning the direction and magnitude of bivariate associations among the variables. We conclude that there is clear evidence of a negative association between the subjective probability of arrest for each crime and the frequency of commission of that crime. We also find some negative cross-effects of the perceptions of the probability of arrest for one type of crime on the commission of another, holding constant the direct effects.